Experimental Study of Tool Life Depending on Cutting Speed for 100CrMn6 Materials & Statistical Processing Using Linear Regression Analysis - Timárová, Ľudmila; Krbaťa, Michal; Kohutiar, Marcel; Escherová, Jana; Jus, Milan (Manufacturing Technology Journal, 2024)
To increase the service life of the cutting tool, various types of coatings are used in modern times, which have a beneficial effect on extending the service life of the tools. Which contributes to reducing the eco-nomic costs of production. The present article examines the effect of cutting speed on the durability of a cutting tool. In the experimental measurements, three types of replaceable cutting inserts were used, without coating, with TiC and TiN coating. The measurements were carried out during technological operations of longitudinal turning on bearing steel 100CrMn6 without the use of coolant. The durability of the cutting discs was evaluated by the method of short-term tests, in which the main evaluation crite-rion was the amount of wear on the back surface of the cutting tool VBBcrit = 0.25 mm. For the statistical processing of the measured results, a detailed mathematical calculation was performed using the meth-od of least squares to determine the parameters of the linear regression function.
Keywords: Durability; Wear; Cutting Speed; Turning; Coating